Commercial poultry and pig farming in Yangon's peri-urban zone - Belton, Ben; Cho, Ame; Payongayong, Ellen; Mahrt, Kristi; Abaidoo, Eric (Michigan State University, 2020)
This report presents results from a comprehensive structured survey of medium and large-scale pig and poultry farms conducted in the peri-urban zone surrounding Yangon. The survey represented pig farms raising five or more breeding sows or 20 or more swine, and all broiler, semi-broiler, and layer farms raising 500 or more birds, in randomly selected villages from 83 village tracts with high concentrations of pig and chicken farms, in Ayeyarwady, Bago (East) and Yangon regions. Owners of 90 pig farms, and 423 poultry farms (290 broiler, 38 semi-broiler, 95 layer) were interviewed. The survey was supported by analysis of nationally representative data on poultry, meat, egg and dairy consumption for 2010 and 2015, poultry, meat, and egg retail prices from 2008 to 2017, and satellite images of peri-urban Yangon for 2014 and 2018. Together, these data sources allow us to characterize the economic and technical dimensions of medium and large-scale pig and poultry farming in Myanmar and recent trends in sectoral growth, to identify implications for policy and development programming. We summarize key findings and discuss their implications below.